Central African Economic and Monetary Community (CEMAC) : Staff Report on the Common Policies in Support of Member Countries Reform Programs-Press Release, Staff Report, and Statement by the Executive Director. (IMF Staff Country Reports; Country Report ;, 2019)
This paper highlights annual discussions on Central African Economic and Monetary Community's (CEMAC) Common Policies in Support of Member Countries Reform Programs. Tighter macroeconomic and financial policies helped to avert a deeper crisis, and gross external reserves increased more rapidly in recent months, also helped by a stronger implementation of CEMAC foreign exchange regulations. Reforms to support a more diversified and inclusive growth, including by improving governance and the business climate, should gain momentum to make current efforts to buttress the external position of the region sustainable. The outlook for 2019 and beyond foresees further improvement in regional reserves assuming CEMAC countries remain committed to their program objectives and new programs with Cameroon, Central African Republic and Equatorial Guinea could start around end-2019.